Antibacterial and deodorant fiber, preparation method and antibacterial and deodorant socks
By introducing a chitosan-tannic acid cross-linking system and a core layer structure of modified zinc oxide, ZIF-8/tea tree oil composite nanoparticles, as well as ε-polylysine and green tea polyphenols in the shell layer into the fiber, the prepared antibacterial and deodorizing fiber solves the problems of easy shedding of antibacterial agents and short-lasting deodorization, and achieves synergistic enhancement of antibacterial and deodorizing effects.
Patent Information
- Application Number
- CN202510915387.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-10-03
AI Technical Summary
Existing antibacterial and deodorizing fibers have problems such as easy shedding of antibacterial agents, short-lasting deodorizing effects, controversial biosafety, and functional imbalance.
A chitosan-tannic acid cross-linking system was used with modified zinc oxide and ZIF-8/tea tree oil composite nanoparticles to construct a stable structure in the core layer. ε-polylysine and green tea polyphenols were introduced into the shell layer to achieve synergistic antibacterial and deodorizing effects. The antibacterial and deodorizing fibers were prepared by coaxial wet spinning.
It significantly improves the antibacterial and deodorizing effects of the fiber, improves the stability of the antibacterial agent and the deodorizing durability, and achieves synergistic enhancement of antibacterial and deodorizing effects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fiber technology, in particular to an antibacterial and deodorizing fiber, a preparation method and antibacterial and deodorizing socks. Background Art
[0002] With the development of functional textiles, demand for antimicrobial and deodorizing fibers continues to grow in areas such as hygiene and care, sportswear, and military equipment. To address issues such as sweat accumulation, bacterial growth, and odor generation, existing antimicrobial and deodorizing fibers primarily achieve their antibacterial and deodorizing properties by incorporating antimicrobial agents, adsorbents, or fragrance encapsulating materials. Common antimicrobial components include nanosilver, nanozinc oxide, chitosan, polyphenolic plant extracts, and their combined systems. Fibers are typically prepared using single-component blended spinning or imparted functionality through padding or coating during the finishing stage.
[0003] However, existing technologies have many limitations. First, traditional antimicrobial finishing methods are mostly surface treatments, and the active ingredients are easily lost due to washing and friction, resulting in poor antimicrobial durability and difficulty meeting the durability requirements of frequently used textiles. Second, volatile fragrances or plant essential oils introduced to enhance deodorization are usually added by physical adsorption or emulsion dispersion. During the spinning process, they are prone to volatilization or uneven coating, resulting in low drug loading efficiency and short deodorization time. Third, some inorganic antimicrobial agents (such as nanosilver) have certain biosafety controversies, especially in applications of skin-friendly fabrics, facing the dual challenges of regulation and consumer acceptance. In addition, if the antimicrobial and deodorizing components fail to achieve structural synergy or release synergy, functional imbalances often occur, such as effective antimicrobial properties but poor deodorization, or significant initial deodorization but rapid antimicrobial decay. Summary of the Invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes an antibacterial and deodorizing fiber, a preparation method and antibacterial and deodorizing socks. The prepared fiber has excellent antibacterial and deodorizing properties.
[0005] The present invention provides a method for preparing an antibacterial and deodorizing fiber, and the method comprises the following steps: S1: chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde are fully dispersed in water to obtain a core layer solution; S2: fully dispersing polyvinyl alcohol, ε-polylysine and green tea polyphenols in water to obtain a shell solution; S3: The core layer solution and the shell layer solution are injected into a coagulation bath by a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
[0006] Preferably, the mass ratio of chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde is 1:0.05-0.15:0.4-0.8:0.05-0.1:0.05-0.1:0.01-0.1.
[0007] Preferably, the mass ratio of polyvinyl alcohol, ε-polylysine and green tea polyphenols is 1:0.01-0.05:0.01-0.05.
[0008] Preferably, the flow rate ratio of the shell solution to the core solution is 1:1-3; the coagulation bath is a mixture of ammonium sulfate, ethanol, sodium hydroxide and water; and the temperature of the coagulation bath is 40-60°C.
[0009] Preferably, the preparation method of ZIF-8 / tea tree essential oil is as follows: tea tree essential oil and zinc nitrate hexahydrate are dispersed in an N,N-dimethylformamide aqueous solution, and then mixed with a 2-methylimidazole solution for reaction. The reaction product is separated, washed and dried to obtain ZIF-8 / tea tree essential oil.
[0010] Preferably, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:5-10; the mass ratio of zinc nitrate hexahydrate to tea tree essential oil is 1:0.5-1.5; the reaction temperature is 20-30° C., and the reaction time is 2-4 hours.
[0011] Preferably, the preparation method of the modified zinc oxide is as follows: dibutyltin dilaurate, nano zinc oxide and ethanol aqueous solution are added to a mixed solution of ethyl glycolate and isocyanatepropyltriethoxysilane to react, and the reaction product is washed and dried to obtain modified nano zinc oxide.
[0012] Preferably, the mass ratio of nano zinc oxide, ethyl glycolate, isocyanatepropyltriethoxysilane and dibutyltin dilaurate is 1:1-1.2:4-6:0.01-0.05; the reaction temperature is 50-70° C., the time is 8-12 h, and the pH of the reaction system is 9-11.
[0013] The antibacterial and deodorizing fiber proposed by the present invention is prepared by adopting the above-mentioned preparation method.
[0014] The present invention provides an antibacterial and deodorizing sock, which is made from the above-mentioned antibacterial and deodorizing fiber.
[0015] Beneficial technical effects of the present invention: The present invention introduces a chitosan-tannic acid cross-linking system into the core layer. This system forms hydrogen bonds and electrostatic complexation between the amino groups on the chitosan molecular chain and the polyphenolic hydroxyl groups of the tannic acid, thereby constructing a stable composite network structure. At the same time, modified zinc oxide and ZIF-8 / tea tree essential oil composite nanoparticles are introduced, and the nano-ZnO is surface-modified by isocyanatepropyltriethoxysilane. This not only improves its dispersion stability and interfacial compatibility in the aqueous phase system, but also constructs a synergistic deodorization and antifungal mechanism with ZIF-8 / tea tree essential oil, significantly improving the antibacterial and deodorizing effects of the fiber.
[0016] The present invention introduces ε-polylysine and green tea polyphenols into the shell layer, further achieving synergistic enhancement of surface antibacterial and odor control. ε-polylysine is a natural cationic polypeptide that rapidly adsorbs bacterial cells and destroys their membrane potential, resulting in rapid sterilization. This, combined with the cationic properties of chitosan, forms a synergistic charge attack mechanism. Green tea polyphenols not only possess antioxidant and deodorizing properties but also complex with protein-based odorants, effectively adsorbing volatile nitrogen- and sulfur-containing odor molecules like ammonia and methyl mercaptan, enhancing the fiber's deodorizing properties. Furthermore, green tea polyphenols form hydrogen bond complexes with PVA in the shell layer, improving the fiber's film-forming properties and surface stability. DETAILED DESCRIPTION
[0017] The present invention will be further explained below with reference to specific embodiments.
[0018] Example 1
[0019] Chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde are fully dispersed in water to obtain a core layer solution; polyvinyl alcohol, ε-polylysine and green tea polyphenols are fully dispersed in water to obtain a shell layer solution; the core layer solution and the shell layer solution are injected into a coagulation bath through a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
[0020] The mass ratio of chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde is 1:0.1:0.6:0.08:0.08:0.05; the mass fraction of chitosan in the core layer solution is 5%.
[0021] The mass ratio of polyvinyl alcohol, ε-polylysine and green tea polyphenols is 1:0.03:0.03; the mass fraction of polyvinyl alcohol in the shell solution is 20%.
[0022] The flow rate ratio of the shell solution to the core solution is 1:2; the coagulation bath is a mixture of ammonium sulfate, ethanol, sodium hydroxide and water; and the temperature of the coagulation bath is 50°C.
[0023] The preparation method of ZIF-8 / tea tree essential oil is as follows: tea tree essential oil and zinc nitrate hexahydrate are dispersed in an N,N-dimethylformamide aqueous solution, and then mixed with a 2-methylimidazole solution for reaction. The reaction product is separated, washed and dried to obtain ZIF-8 / tea tree essential oil.
[0024] The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8; the mass ratio of zinc nitrate hexahydrate to tea tree essential oil is 1:1; the reaction temperature is 25° C., and the reaction time is 3 hours.
[0025] The preparation method of modified zinc oxide is as follows: dibutyltin dilaurate, nano zinc oxide and ethanol aqueous solution are added to a mixed solution of ethyl glycolate and isocyanatepropyltriethoxysilane to react, and the reaction product is washed and dried to obtain modified nano zinc oxide.
[0026] The mass ratio of nano zinc oxide, ethyl glycolate, isocyanatepropyltriethoxysilane and dibutyltin dilaurate is 1:1.1:5:0.03; the reaction temperature is 60°C, the time is 10 hours, and the pH of the reaction system is 10.
[0027] Example 2
[0028] Chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde are fully dispersed in water to obtain a core layer solution; polyvinyl alcohol, ε-polylysine and green tea polyphenols are fully dispersed in water to obtain a shell layer solution; the core layer solution and the shell layer solution are injected into a coagulation bath through a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
[0029] The mass ratio of chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde is 1:0.05:0.4:0.05:0.05:0.01; the mass fraction of chitosan in the core layer solution is 5%.
[0030] The mass ratio of polyvinyl alcohol, ε-polylysine and green tea polyphenols is 1:0.01:0.01; the mass fraction of polyvinyl alcohol in the shell solution is 20%.
[0031] The flow rate ratio of the shell solution to the core solution is 1:1; the coagulation bath is a mixture of ammonium sulfate, ethanol, sodium hydroxide and water; and the temperature of the coagulation bath is 40°C.
[0032] The preparation method of ZIF-8 / tea tree essential oil is as follows: tea tree essential oil and zinc nitrate hexahydrate are dispersed in an N,N-dimethylformamide aqueous solution, and then mixed with a 2-methylimidazole solution for reaction. The reaction product is separated, washed and dried to obtain ZIF-8 / tea tree essential oil.
[0033] The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:5; the mass ratio of zinc nitrate hexahydrate to tea tree essential oil is 1:0.5; the reaction temperature is 20° C., and the reaction time is 2 h.
[0034] The preparation method of modified zinc oxide is as follows: dibutyltin dilaurate, nano zinc oxide and ethanol aqueous solution are added to a mixed solution of ethyl glycolate and isocyanatepropyltriethoxysilane to react, and the reaction product is washed and dried to obtain modified nano zinc oxide.
[0035] The mass ratio of nano zinc oxide, ethyl glycolate, isocyanatepropyltriethoxysilane and dibutyltin dilaurate is 1:1:4:0.01; the reaction temperature is 50°C, the time is 8 hours, and the pH of the reaction system is 9.
[0036] Example 3
[0037] Chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde are fully dispersed in water to obtain a core layer solution; polyvinyl alcohol, ε-polylysine and green tea polyphenols are fully dispersed in water to obtain a shell layer solution; the core layer solution and the shell layer solution are injected into a coagulation bath through a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
[0038] The mass ratio of chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde is 1:0.15:0.8:0.1:0.1:0.1; the mass fraction of chitosan in the core layer solution is 5%.
[0039] The mass ratio of polyvinyl alcohol, ε-polylysine and green tea polyphenols is 1:0.05:0.05; the mass fraction of polyvinyl alcohol in the shell solution is 20%.
[0040] The flow rate ratio of the shell solution to the core solution is 1:3; the coagulation bath is a mixture of ammonium sulfate, ethanol, sodium hydroxide and water; and the temperature of the coagulation bath is 60°C.
[0041] The preparation method of ZIF-8 / tea tree essential oil is as follows: tea tree essential oil and zinc nitrate hexahydrate are dispersed in an N,N-dimethylformamide aqueous solution, and then mixed with a 2-methylimidazole solution for reaction. The reaction product is separated, washed and dried to obtain ZIF-8 / tea tree essential oil.
[0042] The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:10; the mass ratio of zinc nitrate hexahydrate to tea tree essential oil is 1:1.5; the reaction temperature is 30° C. and the reaction time is 4 hours.
[0043] The preparation method of modified zinc oxide is as follows: dibutyltin dilaurate, nano zinc oxide and ethanol aqueous solution are added to a mixed solution of ethyl glycolate and isocyanatepropyltriethoxysilane to react, and the reaction product is washed and dried to obtain modified nano zinc oxide.
[0044] The mass ratio of nano zinc oxide, ethyl glycolate, isocyanatepropyltriethoxysilane and dibutyltin dilaurate is 1:1.2:6:0.05; the reaction temperature is 70°C, the time is 12h, and the pH of the reaction system is 11.
[0045] Comparative Example 1
[0046] Chitosan, tannic acid, glacial acetic acid, ZIF-8 / tea tree essential oil and glutaraldehyde are fully dispersed in water to obtain a core layer solution; polyvinyl alcohol, ε-polylysine and green tea polyphenols are fully dispersed in water to obtain a shell layer solution; the core layer solution and the shell layer solution are injected into a coagulation bath through a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
[0047] The mass ratio of chitosan, tannic acid, glacial acetic acid, ZIF-8 / tea tree essential oil and glutaraldehyde is 1:0.1:0.6:0.16:0.05; the mass fraction of chitosan in the core layer solution is 5%.
[0048] The remaining conditions are the same as those in Example 1.
[0049] Comparative Example 2
[0050] Chitosan, tannic acid, glacial acetic acid, modified zinc oxide and glutaraldehyde are fully dispersed in water to obtain a core layer solution; polyvinyl alcohol, ε-polylysine and green tea polyphenol are fully dispersed in water to obtain a shell layer solution; the core layer solution and the shell layer solution are injected into a coagulation bath through a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
[0051] The mass ratio of chitosan, tannic acid, glacial acetic acid, modified zinc oxide and glutaraldehyde is 1:0.1:0.6:0.16:0.05; the mass fraction of chitosan in the core layer solution is 5%.
[0052] The remaining conditions are the same as those in Example 1.
[0053] Comparative Example 3
[0054] Chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde are fully dispersed in water to obtain a core layer solution; polyvinyl alcohol and green tea polyphenols are fully dispersed in water to obtain a shell layer solution; the core layer solution and the shell layer solution are injected into a coagulation bath through a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
[0055] The mass ratio of polyvinyl alcohol to green tea polyphenols is 1:0.03; the mass fraction of polyvinyl alcohol in the shell solution is 20%.
[0056] The remaining conditions are the same as those in Example 1.
[0057] Comparative Example 4
[0058] Chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde are fully dispersed in water to obtain a core layer solution; polyvinyl alcohol and ε-polylysine are fully dispersed in water to obtain a shell layer solution; the core layer solution and the shell layer solution are injected into a coagulation bath through a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
[0059] The mass ratio of polyvinyl alcohol to ε-polylysine is 1:0.03:0.03; the mass fraction of polyvinyl alcohol in the shell solution is 20%.
[0060] The remaining conditions are the same as those in Example 1.
[0061] The fibers prepared in Example 1 and Comparative Examples 1-4 were woven into fabrics, and the antibacterial, deodorizing, and stability properties of the fabrics were tested. The antibacterial properties were tested in accordance with GB / T 20944.3-2008. The deodorizing properties were tested by placing a 100 mm x 100 mm fabric in a container and injecting hydrogen sulfide gas at a concentration of 3.5 ppm. After 10 minutes, the hydrogen sulfide concentration was measured and the deodorization rate was calculated.
[0062] Table 1 Fiber performance test results
[0063] It can be seen from the test results of Example 1 and Comparative Examples 1-2 in Table 1 that the present invention introduces a chitosan-tannic acid cross-linking system into the core layer, which forms hydrogen bonds and electrostatic complexes between the amino groups on the chitosan molecular chain and the polyphenolic hydroxyl groups of tannic acid, thereby constructing a stable composite network structure. At the same time, modified zinc oxide and ZIF-8 / tea tree oil composite nanoparticles are introduced, and the nano-ZnO is surface-modified by isocyanatepropyltriethoxysilane, which not only improves its dispersion stability and interfacial compatibility in the aqueous phase system, but also can construct a synergistic deodorization and antifungal mechanism with ZIF-8 / tea tree oil, significantly improving the antibacterial and deodorizing effect of the fiber.
[0064] Furthermore, the test results of Example 1 and Comparative Examples 3-4 in Table 1 demonstrate that the present invention, by introducing ε-polylysine and green tea polyphenols into the shell layer, further achieves synergistic enhancement of surface antibacterial and odor control. ε-polylysine, a naturally occurring cationic polypeptide, rapidly adsorbs bacterial cells and rapidly kills bacteria by disrupting their membrane potential. This, combined with the cationic properties of chitosan, forms a synergistic charge attack mechanism. Green tea polyphenols not only possess antioxidant and deodorizing properties but also complex with protein-based odorants, effectively adsorbing volatile nitrogen- and sulfur-containing odor molecules like ammonia and methyl mercaptan, enhancing the fiber's deodorizing properties. Furthermore, green tea polyphenols form hydrogen bond complexes with the PVA in the shell layer, improving the fiber's film-forming properties and surface stability.
[0065] Although the embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present application. The scope of the present application is defined by the appended claims and their equivalents, and all should be included in the scope of protection of the present application.
Claims
1. A method for preparing antibacterial and deodorizing fibers, characterized in that: The steps are as follows: S1: chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde are fully dispersed in water to obtain a core layer solution; S2: fully dispersing polyvinyl alcohol, ε-polylysine and green tea polyphenols in water to obtain a shell solution; S3: The core layer solution and the shell layer solution are injected into a coagulation bath by a coaxial wet spinning method to produce an antibacterial and deodorizing fiber.
2. The method for preparing the antibacterial and deodorizing fiber according to claim 1, characterized in that: The mass ratio of chitosan, tannic acid, glacial acetic acid, modified zinc oxide, ZIF-8 / tea tree essential oil and glutaraldehyde is 1:0.05-0.15:0.4-0.8:0.05-0.1:0.05-0.1:0.01-0.
1.
3. The method for preparing the antibacterial and deodorizing fiber according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol, ε-polylysine and green tea polyphenols is 1:0.01-0.05:0.01-0.
05.
4. The method for preparing the antibacterial and deodorizing fiber according to claim 1, wherein: The flow rate ratio of the shell solution and the core solution is 1:1-3; the coagulation bath is a mixture of ammonium sulfate, ethanol, sodium hydroxide and water; and the temperature of the coagulation bath is 40-60°C.
5. The method for preparing the antibacterial and deodorizing fiber according to claim 1, characterized in that: The preparation method of ZIF-8 / tea tree essential oil is as follows: tea tree essential oil and zinc nitrate hexahydrate are dispersed in an N,N-dimethylformamide aqueous solution, and then mixed with a 2-methylimidazole solution for reaction. The reaction product is separated, washed and dried to obtain ZIF-8 / tea tree essential oil.
6. The method for preparing the antibacterial and deodorizing fiber according to claim 5, characterized in that: The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:5-10; the mass ratio of zinc nitrate hexahydrate to tea tree essential oil is 1:0.5-1.5; the reaction temperature is 20-30° C., and the reaction time is 2-4 hours.
7. The method for preparing the antibacterial and deodorizing fiber according to claim 1, characterized in that: The preparation method of modified zinc oxide is as follows: dibutyltin dilaurate, nano zinc oxide and ethanol aqueous solution are added to a mixed solution of ethyl glycolate and isocyanatepropyltriethoxysilane to react, and the reaction product is washed and dried to obtain modified nano zinc oxide.
8. The method for preparing the antibacterial and deodorizing fiber according to claim 7, characterized in that: The mass ratio of nano zinc oxide, ethyl glycolate, isocyanatepropyltriethoxysilane and dibutyltin dilaurate is 1:1-1.2:4-6:0.01-0.05; the reaction temperature is 50-70°C, the time is 8-12 hours, and the pH value of the reaction system is 9-11.
9. An antibacterial and deodorizing fiber, characterized in that: The method is prepared according to any one of claims 1 to 8. 10.An antibacterial and deodorizing socks, characterized in that: It is made by using the antibacterial and deodorizing fiber described in claim 9.
Citation Information
Cited By
Preparation method of heterocycle-containing polyamide composite fiber
CN121183442A
